(untitled) (Journal of Health Sciences, 2017)
Ampullary cancer is a rare neoplasm of the pancreaticobiliary tract. Most of the ampullary neoplasms require surgical resection. Cephalic pancreaticoduodenectomy (CPD) has been performed laparoscopically at high-volume institutions worldwide. In this paper, we present a 63-year-old patient with painless jaundice, subjected to proximal endoscopy and biopsy of the lesion located in the papilla of Vater, which resulted in a diagnosis of the adenocarcinoma of the papilla of Vater. We performed laparoscopic CPD with appropriate lymphadenectomy. To the best of our knowledge, this complex and technically challenging surgical procedure is the first of this kind in our country and the region.